2023
DOI: 10.1002/gj.4863
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial development and technological innovations on renewable energy consumption: Do the roles of economic openness and financial stability matter in BRICS economies?

Seyed Alireza Athari

Abstract: There is a significant gap in comprehensively probing the determinants of renewable energy consumption (REN) in developing markets. Extant literature suggests the beneficial role of using renewable energy in diminishing carbon emissions and increasing environmental quality. This work addresses this gap and contributes by investigating the factors which significantly affect the REN in emerging economies. More specifically, the present study attempts to contribute by probing the effects of economic openness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Most studies propose eco‐friendly technology as the potential remedy to overcome extreme emissions. However, there is a debate on its indirect or direct heterogeneous impact on CO 2 E. For instance, Athari (2023) and Obobisa et al (2022) integrated the effect of eco‐friendly technology on the climate with economic development for African realms. They found that green technology is not responding in low‐income regions, but in high‐income realms, it strongly influences improving environmental quality.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…Most studies propose eco‐friendly technology as the potential remedy to overcome extreme emissions. However, there is a debate on its indirect or direct heterogeneous impact on CO 2 E. For instance, Athari (2023) and Obobisa et al (2022) integrated the effect of eco‐friendly technology on the climate with economic development for African realms. They found that green technology is not responding in low‐income regions, but in high‐income realms, it strongly influences improving environmental quality.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…A few existing studies have examined demand-side influencing factors, and the available literature mainly covers indicators including resident demand [ 10 , 11 ], renewable energy consumption [ [12] , [13] , [14] ], and electricity consumption [ 15 , 16 ]. Among them, the resident demand level is the most representative of the level of overall demand-side development [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%